PARTISIPASI PEREMPUAN DALAM PROSES RUKYAT HILAL UNTUK PENENTUAN AWAL BULAN HIJRIYAH DI KOTA MAKASSAR - Oktaviana, Selvi; Laman, Ilham (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract This research discusses women's participation in the Rukyat Hilal process to determine the start of the Hijriyah month in Makassar City. This research uses research (field research) using qualitative methods. The approach used by the author is a syar'i approach and a sociological approach. According to the data source, the data in this research is divided into two data, namely primary data and secondary data. Women's participation in the rukyat Hilal process in Makassar City shows a variety of views, with some opinions supporting women's participation without exception, while others highlight individual abilities and capacities rather than just gender. The public's perception of women's participation in the rukyat Hilal process in Makassar City shows an inclusive attitude towards gender roles in religious activities. The community sees women's participation as a positive step to broaden understanding about determining the start of the Hijriyah month, without being limited by gender factors. Supporting factors for women's participation in the Hilal rukyat process include a high level of education, increased gender awareness, women's leadership in religious communities, and an inclusive religious mindset. However, there are also inhibiting factors such as traditions and social norms, lack of awareness of women's rights, gender discrimination, and an imbalance of power between men and women in religious structures. The implication of this research is to further support women's participation in the rukyat Hilal process such as raising awareness and wider education on women's rights and the importance of gender inclusion in religious activities and supporting women's leadership development in religious communities by providing equal opportunities to participate in decision-making and important roles in the rukyat Hilal process.